TLR2-Bound Cancer-Secreted Hsp70 Induces MerTK-Mediated Immunosuppression and Tumorigenesis in Solid Tumors - Kaynak, Ahmet; Vallabhapurapu, Subrahmanya D; Davis, Harold W; Smith, Eric P; Muller, Petr; Vojtesek, Borek; Franco, Robert S; Shao, Wen-Hai; Qi, Xiaoyang (Cancers, 2025)
Background: A hallmark of cancer is the presence of an immunosuppressive tumor microenvironment (TME). Immunosuppressive M2 macrophages (MΦs) in the TME facilitate escape from immune surveillance and promote tumor growth; therefore, TME-induced immunosuppression is a potent immunotherapeutic approach to treating cancer. Methods: Cancer cell-secreted proteins were detected by using liquid chromatography-mass spectrometry (LC-MS). Neutralizing antibodies (nAbs) were used to assess which proteins were involved in MΦs polarization and differentiation. The protein-protein interaction was characterized using co-immunoprecipitation and immunofluorescence assays. Cancer-secreted heat shock protein 70 (Hsp70) protein was quantified using an enzyme-linked immunosorbent assay (ELISA). MΦ polarization and tumor growth were assessed in vivo with subcutaneous LLC-GFP tumor models and toll-like receptor 2 (TLR2) knockout mice; in vitro assessments were conducted using TLR2 knockout and both LLC-GFP and LN227 lentiviral-mediated knockdown (KD) cells. Results: Cancer cells released a secreted form of Hsp70 that acted on MΦ TLR2 to upregulate Mer receptor tyrosine kinase (MerTK) and induce MΦ M2 polarization. Hsp70 nAbs led to a reduction in CD14 expression by 75% in THP-1 cells in response to Gli36 EMD-CM. In addition, neutralizing TLR2 nAbs resulted in a 30% and 50% reduction in CD14 expression on THP-1 cells in response to MiaPaCa-2 and Gli36 exosome/microparticle-depleted conditioned media (EMD-CMs), respectively. Hsp70, TLR2, and MerTK formed a protein complex. Tumor growth and intra-tumor M2 MΦs were significantly reduced upon cancer cell Hsp70 knockdown and in TLR2 knockout mice. Conclusions: Cancer-secreted Hsp70 interacts with TLR2, upregulates MerTK on MΦs, and induces immunosuppressive MΦ M2 polarization. This previously unreported action of secreted Hsp70 suggests that disrupting the Hsp70-TLR2-MerTK interaction could serve as a promising immunotherapeutic approach to mitigate TME immunosuppression in solid cancers.
Keywords: Hsp70; TLR2; phospho-Hsp70; MerTK; cancer; M2 macrophage polarization